2009
DOI: 10.1111/j.1600-0404.1966.tb02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Double Cystometry in the Uninhibited Neurogenic Bladder

Abstract: Various methods have been employed in cystometry. I t has been done by isotonic and isometric measurements, and measurements of both the pressure and the filling of the bladder have been used, either continuously or discontinuously.I n several Danish hospitals, modifications of the method devised by Povlsen (1942) are used. By this method, the intravesical pressure is transmitted through a catheter inserted per urethram, via a pressure chamber, to a manometer. Modifications of this method have previously been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In the present study, we did not find a reduction in unstable detrusor contractions in the second fill as has previously been described. 3,8,9 The signs of urodynamic stress incontinence or detrusor overactivity were highly reproducible. Several previous studies have shown that detrusor overactivity cannot always be detected in patients, despite clear symptoms of urgency, frequency, and urge incontinence.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, we did not find a reduction in unstable detrusor contractions in the second fill as has previously been described. 3,8,9 The signs of urodynamic stress incontinence or detrusor overactivity were highly reproducible. Several previous studies have shown that detrusor overactivity cannot always be detected in patients, despite clear symptoms of urgency, frequency, and urge incontinence.…”
Section: Discussionmentioning
confidence: 96%
“…[19][20][21] Ten to one hundred milliliter per minute cystometry appears to be as useful as registration during physiological filling to describe the maximum detrusor pressure and the mean duration of contraction in patients with a spinal NDO. 24,25 Furosemidestimulated filling cystometry (FCMG) seems to provide more reliable informations that conventional cystometry on detrusor characteristics (maximum detrusor pressure and compliance) in NDO but not in hyporeflexic or areflexic neurogenic bladder. 26 UDS should be performed in supine position on a padded table in complete SCI patients.…”
Section: Invasive Urodynamic Consist Inmentioning
confidence: 99%
“…Rose (1936) reported that repeated cystometries increased intravesical pressure and decreased capacity in a few normal persons. Grynderup (1966) found unaltered capacity of the uninhibited neurogenic bladder at the second filling when the iilling was discontinued at the first detrusor contraction. In intact cats, Klevmark (1977) usually found less increase in intravesical pressure at the second filling to the same volume, when a high and non-physiological.…”
mentioning
confidence: 89%
“…To what extent the capacity of the human bladder is dependent on the 'filling rate is a matter of controversy. Grynderup (1966) who investigated uninhibited bladders, found decreased capacity when cystometry was repeated at a filling rate higher than at the 6rst 6lling. Lungworthy et al (1936) in studies on the uninhibited bladder, Cass et al (1970) in normal bladder and Ramsden et al (1977) in both types of bladders, found that the capacity was independent of the filling rate.…”
mentioning
confidence: 99%